2019
DOI: 10.1029/2019jc015631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anticyclonic Eddies on the Multicore Structure of the North Pacific Subtropical Mode Water Based on Argo Observations

Abstract: The North Pacific subtropical mode water (STMW) often displays a “multicore structure” with more than one minimum in the vertical potential vorticity profile. Anticyclonic eddies (AEs) play an important role in STMW formation and transport, but their effect on the multicore structure of the STMW has not been fully studied. Here, we investigated the formation and evolution of STMW multicore structures in AEs using Argo profiles, which followed two AEs in the STMW formation region for approximately 1.5 years fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This definition differs from that used in our previous studies using Argo profiles, i.e., a layer where Q is lower than 2.0 × 10 -10 m −1 s −1 and θ at the Q minimum (called core θ hereafter) is between 16 and 19.5 °C (Oka 2009;Oka et al 2011Oka et al , 2015. In the new definition, we permit the existence of more than one STMW layer in each profile, which has been frequently observed in mode waters (Taneda et al 2000;Oka et al 2011Oka et al , 2020Gao et al 2016;Liu et al 2017Liu et al , 2019. It should also be noted that the θ range for the STMW definition is different between the 137ºE and Argo float data; the narrower and relatively warm θ range for the more contemporary Argo data reflects long-term warming of STMW (Sugimoto et al 2017;Oka et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This definition differs from that used in our previous studies using Argo profiles, i.e., a layer where Q is lower than 2.0 × 10 -10 m −1 s −1 and θ at the Q minimum (called core θ hereafter) is between 16 and 19.5 °C (Oka 2009;Oka et al 2011Oka et al , 2015. In the new definition, we permit the existence of more than one STMW layer in each profile, which has been frequently observed in mode waters (Taneda et al 2000;Oka et al 2011Oka et al , 2020Gao et al 2016;Liu et al 2017Liu et al , 2019. It should also be noted that the θ range for the STMW definition is different between the 137ºE and Argo float data; the narrower and relatively warm θ range for the more contemporary Argo data reflects long-term warming of STMW (Sugimoto et al 2017;Oka et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Water pycnostads and thought to be formed by interleaving of mode waters with different densities (Oka et al 2011b) or by formation of a lighter mode water over a preexisting denser mode water (Liu et al 2017(Liu et al , 2019. In our cruises in 2013 and 2016, they were observed in 38% of TRMW/D-CMW pycnostads in the 41° N-west section in mid-April, Fig.…”
Section: Multiple Cores Have Been Observed In Subtropical Modementioning
confidence: 56%
“…In each pycnostad, the core, defined as a Q minimum, is considered to be the least modified portion since the pycnostad was formed, thus best preserving the water properties at the time of formation while the pycnostad is modified through mixing with surrounding water (Talley and Raymer 1982;Suga et al 1989). Observations of Subtropical Mode Water (Masuzawa 1969) south of the Kuroshio Extension have demonstrated that pycnostads sometimes have two or more cores (Taneda et al 2000;Oka et al 2011b;Gao et al 2016;Liu et al 2017Liu et al , 2019, as observed in those in Eddies A, B, and C (Figs. 2d, e, 4d, e).…”
Section: Distribution and Characteristics Of Pycnostads In The Zonal Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the Argo float #2901551 left the STMW in April 7, 2014 (Figure 6). The STMW formed during spring storms inside AE14 would be trapped and transported southwestward by AE14 (Liu et al, 2019;Xu et al, 2017).…”
Section: The Ae14 Case Studymentioning
confidence: 99%